ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP PARTISIPASI ANGGOTA KOPERASI UNIT DESA (KUD) SAWIT JAYA KECAMATAN BANGKINANG KABUPATEN KAMPAR - Anggraini, Irda Luvia; Nas, Sakdanur; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted aimed at knowing the effect of service quality on the participation of members of the Village Unit Cooperative (KUD) of Sawit Jaya District bangkinang Kampar Regency. The population in this study was members domiciled in Bukit Payung Village, Laboy Jaya Village, Desa Sembilan and Suka Mulya Village which numbered 1619 people. A sample of 95 people was taken with the Slovin formula with Purposive Sampling technique. Data analysis techniques using Validity Test, Reliability Test, Nomality Test. Then the data is analyzed with simple linear regression, Test F and Determination Coefficient to find out the quality of service of partitioned members. Based on the research obtained the results of a simple linear regression analysis where the calculation results showed F-calculate > F-table (Fcaltung 29,775 > Ftabel 3.94) and the effect of service quality on the participation of kud sawit jaya members was 24.3% while the rest was influenced by other factors not studied in the.Key Words: Quality of Service, Member participation